Aerial and ground fungicide application to corn for disease control - Cunha, João (2010)
This study aimed to evaluate the effect of the aerial and ground application of fungicide in the control of corn diseases and in the spray deposition on the canopy. The hybrid AG7010 was sown and the spray deposition on the bottom, middle and upper canopy of the crop, disease severity and yield were evaluated after the application of the fungicide (pyraclostrobin + epoxiconazol), at the V8-V10 stage. The aerial application was accomplished with spray volumes of 15 and 30 L ha-1, using flat-fan spray nozzles, and the ground one with 100 L ha-1, using turbo twin flat-fan and air induction turbo flat-fan spray nozzles. An additional treatment that received no fungicide was also evaluated. The study of the deposition was achieved using water sensitive papers. It was concluded that that the conventional treatments presented larger droplet density in the corn canopy; however all of the treatments provided the minimum deposition recommended for fungicide application. The aerial application using spray volume of 30 L ha-1 provided similar yield to the conventional treatments, showing to be technically feasible to use.